2020
DOI: 10.1007/s10803-020-04486-4
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Newly Identified or Diagnosed Autistic Adults: An Initial Evaluation of an Autistic-Led Programme

Abstract: Sixteen adults (diagnosed or self-identified as autistic) participated in one of two iterations of a ten-week autistic-led programme, aimed at helping autistic adults learn more about autism within a peer group context. Motivations for taking part in the programme included a desire for: (1) exploration of autism; (2) empowerment; and (3) the development of practical strategies and coping mechanisms. Interviews were conducted upon completion of the programme and again 6 months later. Using thematic analysis, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 31 publications
3
65
0
Order By: Relevance
“…Specifically, our findings challenge current diagnostic criteria and theoretical framing of autism. The finding that rapport is improved between autistic people strengthens calls for peer support for autistic people (Iemmi, 2017;Crane et al, 2020), particularly since a sense of belonging is a protective factor against suicide (Pelton and Cassidy, 2017). In an educational context, these findings challenge peer mediated support practices which specifically involve pairing autistic children with non-autistic peers who are meant to act as social "role models" (Chang and Locke, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, our findings challenge current diagnostic criteria and theoretical framing of autism. The finding that rapport is improved between autistic people strengthens calls for peer support for autistic people (Iemmi, 2017;Crane et al, 2020), particularly since a sense of belonging is a protective factor against suicide (Pelton and Cassidy, 2017). In an educational context, these findings challenge peer mediated support practices which specifically involve pairing autistic children with non-autistic peers who are meant to act as social "role models" (Chang and Locke, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Although a number of studies have found that services led by autistic individuals can be beneficial for autistic adult outcomes (e.g. Rosqvist, 2019; Crane et al, 2020), it is important to avoid isolating autistic adults into silos. SP services should ensure that they are accessible to whomever wishes to access them, and we suggest that general services which accept and support neurodiversity may have the greatest impact on the well-being of autistic adults.…”
Section: Accessmentioning
confidence: 99%
“…The prototype Research Passport included a section for the researcher to add information about themselves, following the suggestion of a member of our project team (see also Pellicano et al 23 ). Trust between participants and researchers can be fostered by researchers spending time with participants informally, and being willing to provide information about themselves (e.g., their motivations for conducting autism research) 24 . As well as building relationships between researchers and participants, this proposed initiative may address the power imbalance that often hinders autistic people's participation in research 24 .…”
Section: Theme 3 the Usability And Need To Manage Expectations Autistic Adults Andmentioning
confidence: 99%